CircRNA profiling reveals the regulatory role of circPAN3 in Hezuo boars Sertoli cell growth - Haixia Shi; Zunqiang Yan; Hong Du; Bo Zhang; Shuangbao Gun (BMC Genomics)
Abstract Background The Hezuo (HZ) pig, a famous indigenous breed in China, is characterized by precocious puberty compared with foreign-introduced pig breeds. Sexual maturation is a complex physiological process, and in recent years, circular RNAs (circRNAs), a new class of noncoding RNAs with endogenous regulatory functions, have been shown to play important roles in regulating sexual maturation. However, the dynamic expression and regulatory mechanism of circRNAs during sexual maturation in HZ pigs remain unclear. In this study, we performed RNA sequencing and bioinformatics analysis to reveal circRNA expression patterns in the testes of HZ boars at 30 days (sexual immaturity; Ha) and 120 days (sexual maturity; Hb), with Landrace (LC) boars of the same age (La and Lb) as controls. Subsequently, an abundant circ_005678 (circPAN3) transcribed from the PAN3 gene, was functionally investigated by RT-qPCR, Western Blot, CCK-8, and flow cytometry. Results We identified 31,134 circRNAs in 12 samples, and 2,562, 2,401, 749, and 831 differentially expressed (DE) circRNAs were identified in the Ha-vs-Hb, La-vs-Lb, Ha-vs-La, and Hb-vs-Lb groups, respectively. The results of functional enrichment analyses indicated that these source genes of the DE circRNAs were involved mainly in testicular development and spermatogenesis. Furthermore, we constructed a circRNA-miRNA-mRNA interaction network and functionally analyzed the target genes. GO functional annotation of the target genes suggested that they were mainly involved in biological processes such as gland development, cell proliferation, and reproduction. KEGG pathway analysis further revealed that these genes were enriched mainly in signaling pathways involved in testicular development and spermatogenesis, including the PI3K-Akt and MAPK signaling pathways. Cellular assays revealed that circPAN3 promoted proliferation and inhibited apoptosis in immature Sertoli cells, whereas opposite changes were observed by circPAN3 knockdown. Conclusions This study revealed the dynamic expression profiles and regulatory mechanisms of circRNAs during sexual maturation in HZ pigs. Further functional studies demonstrated that circPAN3 promoted the proliferation and inhibited the apoptosis of immature Sertoli cells, suggesting that circPAN3 may be closely related to the characteristics of precocious puberty in HZ boars. These findings provide a new perspective for exploring the regulatory mechanism of circRNAs in precocious puberty in HZ pigs.